Design, synthesis, antibacterial evaluation, molecular docking and computational study of 4-alkoxy/aryloxyphenyl cyclopropyl methane oxime derivatives. (April 2021) - Chaudhary, Aniruddh Prasad; Shukla, Akhilesh Kumar; Kant, Padam
Graphical abstract: Highlights: The compounds (2 h ) and (2k ) were found to exhibit excellent activity because these compounds have furyl, and pyridinyl group. The synthesized compound has higher HOMO-LUMO energy gap (5.0774 eV) which indicates that the compound (2k ) is more stable and chemically less reactive. The first static hyperpolarizability ( β 0 ) of (2k) is calculated as 5.06   ×   10 - 30 esu (gas phase), 6.29   ×   10 - 30 e s u CHCl3 ), 6.80   ×   10 - 30 esu (CH2 Cl2 ), 7.31   ×   10 - 30 esu (DMSO). In present molecule (2k), a strong interaction observed between the lone pair of O3 (LP(2)) and the anti-bonding acceptor of the benzene ring ( π * (C4-C5)) with the stabilization energy of 29.74 kcal mol −1 Based on the experimental results, molecular docking studies and binding interactions, the (2k ) can be considered as a drug candidate for treating enteric fever as like to the streptomycin. Abstract: A series of new 4-alkoxy/aryloxyphenyl cyclopropyl methane oxime derivatives 2(a–k) were synthesized and fully characterized by FT-IR, 1H-NMR, 13C-NMR and Mass spectrometry techniques. All the synthesized compounds 2(a–k) were assayed for in vitro antibacterial activity against a selected bacterial strain and the compound (2 h ) and (2k ) exerted excellent activity against Staphylococcus aureus, Escherichia coli and Salmonella typhi strains. The potency of inhibitors and possible interaction mechanism of synthetic oxime (2k ) with 1GQN enzyme on Salmonella typhi was explored by molecular docking method. Amongst the all synthesized compounds, the quantum chemical calculations were done for Cyclopropyl(4-(pyridin-3-ylmethoxy)phenyl)methanone oxime (2k ). The first hyperpolarizability calculation performed in different solvent such as CHCl3, CH2 Cl2 and DMSO and compared to the reference compound urea. In addition, natural bond orbital analysis (NBO), local reactivity descriptors, thermodynamic properties, Mulliken charges, molecular electrostatic potential (MEP), frontier molecular orbitals (FMO) analysis were explored using theoretical calculations.